Orzekanie przez organ odwoławczy po upływie terminu przedawnienia w sprawie kary pieniężnej za uszkodzenie, zniszczenie lub usunięcie drzewa lub krzewu bez zezwolenia lub zgłoszenia.: Uwagi na tle wyroków NSA z 22 listopada 2019 r. (II OSK 35/18) i 2 lutego 2024 r. (III OSK 1242/22) - Bochentyn, Adam (PRAWO i WIĘŹ, 2025)
The study focuses on the issue of adjudication by the appellate authority after the expiration of the limitation period in cases involving fines for damage, destruction, or removal of a tree or shrub without a permit or notification. A critical assessment is made of the position taken by the Supreme Administrative Court in rulings II OSK 35/18 and III OSK 1242/22, according to which the appellate authority may substantively resolve the case if the first-instance authority issued a decision before the expiration of the limitation period. It is pointed out that this approach does not take into account the principle of the two-stage procedure and the nature of the appellate procedure, which is not limited to the review of the first instance decision, but also includes the reconsideration and resolution of the case. The study also examines whether compliance with the limitation period requires that the decision of the appellate authority imposing an administrative fine be delivered to the party or whether it is sufficient that it be issued. It was concluded that the decision must be delivered to the party before the expiry of this period.